An evaluation of changes in the bioclimate of Łódź in the light of the tourism climate index - Siedlecki, Mariusz (Turyzm/Tourism, 2015)
The paper presents basic information concerning bioclimatic conditions in Łódź based on the Tourism Climate Index (TCI). The index makes it possible to assess in a comprehensive manner, based on specified meteorological parameters, the climatic conditions affecting the development of tourism. The study uses measurements from the weather station, Łódź-Lublinek, taken in the years 1966-2014. The TCI values have a distinct annual pattern with the highest values recorded in summer. The summer season has the highest frequency of days with ‘very good’ or ‘excellent’ conditions for tourism. An assessment of the variability of bioclimatic conditions indicates an increase in the number of days with high TCI values pointing to ‘very good’ or ‘excellent’ conditions for tourism and recreation.